2019
DOI: 10.1186/s13045-019-0755-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome inhibitors: promising therapeutic approaches against cancer

Abstract: Inflammation has long been accepted as a key component of carcinogenesis. During inflammation, inflammasomes are potent contributors to the activation of inflammatory cytokines that lead to an inflammatory cascade. Considering the contributing role of inflammasomes in cancer progression, inflammasome inhibitors seem to have a promising future in cancer treatment and prevention. Here, we summarize the structures and signaling pathways of inflammasomes and detail some inflammasome inhibitors used to treat variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 139 publications
1
51
0
1
Order By: Relevance
“…Inflammation, one of the major hallmarks of cancer, mediates cancer progression via the coordinated actions of cytokines, chemokines, and innate immune cells [16]. Inflammasomes, cytosolic multiprotein oligomers containing a member of the NOD-like receptor protein (NLRP) family, the apoptosis-associated speck-like protein containing a CARD (ASC), and pro-caspase-1, are responsible for producing active interleukin family cytokines in response to infection and cellular stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, one of the major hallmarks of cancer, mediates cancer progression via the coordinated actions of cytokines, chemokines, and innate immune cells [16]. Inflammasomes, cytosolic multiprotein oligomers containing a member of the NOD-like receptor protein (NLRP) family, the apoptosis-associated speck-like protein containing a CARD (ASC), and pro-caspase-1, are responsible for producing active interleukin family cytokines in response to infection and cellular stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we indicated that the inflammasome may play an important role in non-bacterial prostate inflammation [8], as also suggested in other studies [9][10][11]. In addition, the inflammasome has gradually become a target for treating pain [12] and inflammation [13,14]. However, there is still no definitive treatment targeting the inflammasome in CPPS.…”
Section: Introductionmentioning
confidence: 52%
“…Moreover, Yang et al con rmed that CRP promoted myeloma cell proliferation under stress and protected cancer cells from being damaged by chemotherapy drugs [48]. What's more, Shengchao Xu et al demonstrated that in ammasome inhibitors are helpful in the treatment of in ammationrelated tumors [49]. Clearly, the mechanisms of CRP regarding the progression of B-iNHL need to be clari ed in further investigations.…”
Section: Discussionmentioning
confidence: 99%